Hybrid Encryption Algorithm Based on Spatial and Gray Level Information - Suolan Liu; Chen Chen; Yue Chen; Hongyuan Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Based on the analysis of the defect of traditional image scrambling methods, a new hybrid scrambling algorithm is proposed. It uses image’s spatial and gray level information. Comparative experiments show it has the advantages of easy implementation, large key space, and good scrambling effect by only one time scrambling instead of many times processing.